Study of femoral neck fractures in elderly patients of Malayalam population - Rajasekharan, Jayakrishnan (International Journal of Research in Orthopaedics, 2019)
Background: 53 elderly patients aged between 51 to 80 were operated for fracture of neck of Femur to compare the two methods for early healing. Methods: All patients selected for bipolar hemiarthopalsty. Out of them 25 were cemented, and 28 were un-cemented. Every patients was operated through posterior (Southern- Moore) approach. Harris Hip score was studied to assess the duration of improvement. Results: History of the patients was 12 (22.6%) were diabetic mellitus, 14 (26.4%) were Hypertensive 9 (16.9%) were alcoholic, 18 (33.9%) were normal (NAD) in the comparison of Harris Hip score at different age-in 51-60 years mean value was 92.8, (SD±0.3), in 61-70 years mean value was 85.1 (SD±0.26), in 71-80 years mean value was 81.9 (SD±0.26), On total sum of score was 729.6, DF was 51, MSS was 363, 0.07, F=ratio was 5019, p value was highly significant (p<0.01). In the comparative study of Harris Hip score degrees in both methods were quite functional, chi-square test was 3.90 DF=3, and p>0.05. Conclusions: This study of bipolar hemiartho pasty with cement or without cement will be quite effective to treat the neck fracture in old patients due to its dual fixation because calcar femorale present in the neck of the femur become function less with advancement of age moreover neck of the femur is devoid of periosteum Hence healing of neck fracture of the femur is medical challenge.